The Psychoactive Power of Foods: A Case of Acute Nutmeg Intoxication - Duarte, Desidério (2021)
Ingestion of high doses of nutmeg causes potentially serious and disabling medical and psychiatric consequences. No isolated component of nutmeg has been identified as responsible for all symptoms observed during intoxication, however myristicin, one of the essential oil’s components of this spice, is believed to be responsible for most psychoactive effects, although the exact mechanism is not known. Other constituents, such as elemicin, may also be involved. Symptoms of intoxication begin three to six hours after ingestion, resolve within the first 48 hours, and usually leave no sequelae. In this paper we present the case of a patient who after consuming 18 to 28 g of nutmeg developed a severe psychotic episode, with disorganized speech, psychomotor agitation and mystical/grandiose delusional ideation. The symptoms resolved quickly, and after one year of clinical stability without therapy, was discharged from the specialist consultation.